Interactivity in the principal independent online media in Mexico (2023) - Díaz Cerveró, Elba; Daniel Barredo-Ibáñez; Karen Tatiana Pinto Garzón (My University, 2024)
Based on the hypothesis that independent Mexican digital media outlets are more connected to their audiences than traditional newspapers, the primary objective of this study is to examine the interactivity proposed and provided to users by these independent online media outlets. As secondary objectives, we seek to identify trends in the interface design of the selected media outlets. Lastly, this research aims to compare the levels of interaction present in the sample. To accomplish this, we analyzed 137 Mexican newspapers from the Sembramedia database (2023), applying an interactivity model according to the Rodríguez et al. (2012) model, with a previous adaptation done by the authors and validated through the Kuder-Richardson coefficient (KR20). The main findings reveal that, while there are high levels of interactivity in terms of information accessibility and media presence on Web 2.0 platforms, interactivity remains limited when it comes to user-generated content reproduction, information personalization, and utilization of Web 2.0 tools. Consequently, this study concludes that the analyzed independent digital media outlets still hesitate to relinquish greater control to users. However, their business model continues to prioritize audience loyalty, increasingly relying on subscriptions and, to a lesser extent, government advertising. Furthermore, the findings suggest three crucial factors influencing the evolution of interactivity. Firstly, improving transparency in media-user communication and facilitating user content publication. Secondly, simplifying access and using intuitive tools may enhance user experience, although it could lead to a potential reduction in multimedia content. Lastly, restricting media connections with Web 2.0 platforms suggests centralizing web traffic within the outlet, departing from external platforms that monopolize advertising investment.